Rancang Bangun Ekstension Ckan 2.7 Untuk Open Data Portal Pada Dinas Komunikasi Informatika Dan Persandian Provinsi Aceh - Munawar, Chandra; Akbar, Rizaldi; Fathurrahmad (Jurnal Sistem Komputer (SISKOM), 2026)
The CKAN 2.7 platform provides basic functionality for open data portals; however, it requires customization to meet the specific needs of an organization. This study aims to address the research problem of how to design and implement a CKAN 2.7 extension to enhance the interface and functionality of the Open Data Portal at the Communications, Informatics, and Encryption Agency of Aceh Province. The research method applied is Research and Development (R&D) with a waterfall system development model. The extension was developed using Python, Jinja2, HTML, CSS, and JavaScript, and deployed in a virtual environment (VirtualBox 7.1 with Ubuntu 14.04 OS). The advantages of the successfully developed extension include: integration of local Aceh identity into the user interface, addition of a filtered search feature, improved directory structure, and a more dynamic dashboard display (showing dataset and active user counts). Therefore, this study provides a technical solution that not only meets functional requirements but also strengthens the local branding of the government’s open data portal.